1966
DOI: 10.1055/s-0029-1227940
|View full text |Cite
|
Sign up to set email alerts
|

Technetium99mTc in der Diagnostik von Schilddrüsenerkrankungen

Abstract: M. Wiedermann und O. Charamza 7 Abbildungen os de,-Radioisolopenobledung (Voistand: ¡)r. ,m'd. M. Tliedermonn) des f/n i,'e,sitälskrankenhw, ses Oloinouc/OSSU iiiul dem Zeniralinslitul fur Kernforschung, flosseiidorf (I)irektor: Piof. Dr.-Ing. If. Faulstich) Heruntergeladen von: NYU. Urheberrechtlich geschützt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
6

Year Published

1967
1967
1974
1974

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
3
0
6
Order By: Relevance
“…Measuring the uptake at 30 minutes they found the mean to be 2-46% in normals and 18-2% in thyrotoxic patients. Kuba et al (1966) used potassium perchlorate to block uptake by the thyroid of 9BmTc in order to measure E.N.R., which has the disadvantage of two separate uptake measurements on successive days. It is nevertheless interesting that they found the E.N.R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the uptake at 30 minutes they found the mean to be 2-46% in normals and 18-2% in thyrotoxic patients. Kuba et al (1966) used potassium perchlorate to block uptake by the thyroid of 9BmTc in order to measure E.N.R., which has the disadvantage of two separate uptake measurements on successive days. It is nevertheless interesting that they found the E.N.R.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital Centre, Stoke-on-Trent W. VAN Since then a number of workers have shown that excellent thyroid scans can be obtained with 9mTc (Andros et al, 1965;Degrossi et al, 1965;Kuba et al, 1966;Atkins and Richards, 1968;Haas et al, 1968;Umek and Czembirek, 1968;Crema et al, 1969). Technetium is trapped by the thyroid, as is iodide, but soon after administration no significant organic binding takes place (Andros et al, 1965;Shimmins et al, 1968;Shimmins et al, 1969).…”
Section: Departments Of Endocrinology and Physics North Staffordshirementioning
confidence: 99%
“…Das Pertechnetat verhält sich also gegenüber der normalen Schilddrüse ähnlich wie das Jod bei Blockade mit Propylthiouracil (1,8). Bei Gesunden ist deshalb die Konzentration des Radiopertechnetats verhältnismäßig niedrig und erreicht das Maximum innerhalb von 30 bis 60 Minuten (7,10). Mit Hilfe von Perchlorat läßt sich der Gehalt des in der Schilddrüse gespeicherten Pertechnetats rasch kompetitiv herabsetzen.…”
Section: Besprechungunclassified
“…Nach parenteraler oder peroraler Verabreichung von 99m Tc-Pertechnetat kommt es zu seiner primären Konzentration in der Schilddrüse, in den Speicheldrüsen und im Magen (7,8,11). Die Affinität des Pertechnetats zur Schilddrüse wurde bereits von zahlreichen Autoren für die Szintigraphie ausgenützt (1,3,5,7,8,9,10,12). Börner, Grundberg und Moll zeigten, daß auch die Szintigraphie der Speicheldrüsen mit Hilfe des Radiopertechnetats klinisch bedeutsam sein kann (4).…”
unclassified
See 1 more Smart Citation